MAXIMUM POWER EXTRACTION USING TWISTING SLIDING MODE CONTROLLER FOR WIND ENERGY SYSTEMS - Asaad Abed Faisal; Turki Kahawish Hassan (Journal of Engineering and Sustainable Development, 2023)
This paper presents a systematic control scheme for a wind energy conversion system with variable speed and describes a permanent magnet synchronous generator PMSG with five phases. The machine employs back-to-back converters, while the grid-side converters are used. Stator current and mechanical rotation speed control are employed to accomplish maximum power point tracking operation on the machine side converter at wind speed below the rated speed. The pitch of the angle is used to limit the extracted wind energy when the wind surpasses the specified wind. The grid current control loop regulates both active and reactive power injection at the unity power factor for the grid side converter. The five-phase PMSG rotor speed is controlled by the twisting sliding mode controller in order to maintain the reference speed in various wind speeds. Performance comparisons between the twisting sliding mode controller, conventional proportional integral controller, and integral sliding mode controller show that the twisting sliding mode controller is superior to the other controllers in steady state error. According to this study, the overall efficiency is increased to 94% when using the TSMC controller rather than the ISMC and PI controllers, which are currently at 92.45% and 88.12% respectively. MATLAB/Simulink simulation results are used to verify the effectiveness of the suggested control technique.